Functional Characterization of Hypertrehalosemic Hormone Receptor in Relation to Hemolymph Trehalose and to Oxidative Stress in the Cockroach Blattella germanica - Huang, Jia-Hsin; Belles, Xavier; Lee, How-Jing (Frontiers in Endocrinology, 2012)
Hypertrehalosemic hormone (HTH) is a peptide hormone that belongs to the AKH/RPCH (adipokinetic hormone/red pigment concentrating hormone) family, which exerts pleiotropic actions related to catabolic reaction and stress response. AKH peptides have been demonstrated to participate in stress response including oxidative stress in several insects. In order to study the signaling pathway of HTH involved in anti-oxidative stress, we have characterized a hypertrehalosemic hormone receptor cDNA in Blattella germanica (Blage-HTHR) in structural and in functional terms using RNA interference (RNAi). Blage-HTHR is expressed in various female adult tissues (brain-CC-CA, ventral nerve cord, midgut, fat body, oviduct), but maximal expression is observed in the fat body. RNAi-mediated knockdown of Blage-HTHR expression results in a significantly lower level of hemolymph trehalose, even though HTH is exogenously administered. Paraquat elicits lethal oxidative stress in B. germanica, and co-injection of paraquat and HTH reduces this detrimental effect and extends the median survival time. Interestingly, the “rescue” effect of HTH on mortality caused by paraquat is diminished in specimens with depleted expression of Blage-HTH and Blage-HTHR. Finally, lipid peroxidation in the hemolymph increases 4 h after paraquat treatment, in comparison with control specimens or with HTH-treated specimens. However, lipid peroxidation induced by paraquat was not “rescued” by HTH in Blage-HTH and Blage-HTHR knockdown specimens. Our results demonstrate that HTH acts as a stress hormone mediating anti-oxidative protection in B. germanica, and that its receptor, Blage-HTHR, is essential for this action.